Designing a video consultation area for hybrid care delivery: the Garden Room with a view - Smits, Merlijn; van Dalen, Demi; Popping, Danny; Bleeker, René; Stommel, Martijn W. J.; van Goor, Harry (Frontiers in Digital Health, 2023)
Introduction Accelerated by the coronavirus pandemic, the healthcare landscape is rapidly evolving, with a shift towards hybrid care models combining in-person and online care. To support this shift, the Radboudumc, an academic hospital in the Netherlands, decided to redesign an existing space facilitating the conduction of video consultations. Method The design process involved participation of end-users to ensure that the physical space met their needs. The look and feel of the area was based on evidence-based design guidelines. Two prototype setups were built and tested, and the feedback informed the final design of the Garden Room. Results Identified end-user needs were divided into 3 major categories entailing consultation room setup, optimal use of technology and practical issues involving room availability. Combined with the look and feel of the hospital, final design requirements were developed. The Garden Room consists of 18 video consultation rooms, 4 shared workspaces, relaxation area with kitchen, and meeting rooms. Specific attention is given to the ergonomics, technology and privacy in the rooms to facilitate optimal video conversations between patients and healthcare providers. In the Garden Room, natural elements and an open design supports working in a healing environment. Discussion Next challenge will be optimizing the use of the Garden Room, which may be hindered by various barriers like resistance to change, existing work processes, and lack of skills training. To address these barriers and support use of the Garden Room, the hospital should focus on the implementation of education, changes in work processes, and the presence of advocates for telehealth.